The impact of central sparing on the word-length effect in hemianopia. Issue 7 (16th November 2016) - Rubino, Cristina; Yeung, Shanna C.; Barton, Jason J. S.
ABSTRACT: Studies suggest that a word-length effect of up to 160 ms/letter distinguishes hemianopic dyslexia from pure alexia. However, partial preservation of central vision is common in right hemianopia, but its effects on single-word reading are unknown. Eighteen healthy subjects read single words with a gaze-contingent right hemianopia simulation that varied the degree of central sparing. Mean reading onset time declined with small degrees of central sparing, but the word-length effect did not decrease until sparing exceeded 3.15°. We next evaluated the effects of font size. Effects of central sparing were constant when expressed in number of letters, with a decline in word-length effect beginning as sparing approached 4 letters. We conclude that the effects of central sparing on mean reading onset time and the word-length effect are distinct. We provide diagnostic word-length criteria for discriminating between pure alexia and hemianopic dyslexia with various degrees of central sparing.